Voila! 2 - Papadima-Sophocleous, Salomi (My University, 2003)
YEARS 9 - 10 Voila! is an exciting new French language program written specifically to cover national and state outcomes-based courses. Voila! textbooks are designed as self-contained spreads with high-impact stimulus material, dialogues, language tips, key vocabulary and speaking and listening activities. The books also feature a wide variety of text types, and one of the most comprehensive dictionary and grammar sections ever provided in a French textbook. The Voila! French language program also includes: an all-new workbook featuring a variety of text types, and many new listening, writing and revision activities interactive multimedia CD-ROM with hundreds of hands-on acitivies for students to enjoy as the enhance their skills. Students can record their voice and compare it to a native speaker's, and access all audio files from the textbook and workbook. a website featuring an automated student chatroom where students can talk to the characters in the textbook, a Quizmaster interactive game show, French Internet links and much, much more.
Keywords: French language; Textbook for foreign speakers